An Expressive Therapy Group Disclosure Intervention for Women Living With HIV Improves Social Support, Self‐efficacy, and the Safety and Quality of Relationships: A Qualitative Analysis☆. (March 2015) - Machtinger, Edward L.; Lavin, Sonja M.; Hilliard, Starr; Jones, Rhodessa; Haberer, Jessica E.; Capito, Kristen; Dawson‐Rose, Carol
Abstract : N/A: Women living with HIV (WLHIV) face high rates of morbidity and mortality. HIV disclosure interventions have been identified as a promising but under‐evaluated approach for WLHIV to improve their health and well‐being. The Medea Project is an expressive therapy group intervention that was first developed to help incarcerated women develop the confidence and skills to tell their stories publicly in theatrical performances. The intervention was subsequently adapted as a community‐based disclosure intervention for WLHIV. Our study describes an analysis of the impact of the Medea Project on the lives of the WLHIV who participated. All participating WLHIV publicly disclosed their HIV status during the performances. Five impact themes emerged from the data: sisterhood, catharsis, self‐acceptance, safer and healthier relationships, and gaining a voice. Our study identifies a voluntary, effective, and broadly beneficial disclosure intervention for women living with HIV.